R.A. Maslov on Franco-Burgundian Relations in the Second Half of the 15th Century - N. A. Bessilin; G. F. Sanzharova (Научный диалог)
The characteristic of the Franco-Burgundian relations of the second half of the 15th century in the works of R. A. Maslov is considered. It is noted that the research problem does not need additional actualization: the time under study was a turning point in the history of France, the final stage in the formation of a centralized state. It is shown that the experience of many years of work of R. A. Maslov confirmed the conclusions that during several decades of the reign of Louis XI significant success was achieved in creating a modern French state, the foundations were created for the economic and political unification of its territory, for the cultural and linguistic community of the population and, accordingly, conditions are provided for the formation of the French nation. The attention of R. A. Maslov to the fact that the most important prerequisite for the formation of a nation was the achievement of political unity of the country, carried out on the basis of the creation of its economic community. It is indicated that in his studies Maslov argues the point of view according to which the fierce struggle for the elimination of feudal fragmentation reflected the process of economic consolidation of individual regions of the country into a single whole and the creation of an all-French internal market.